Patients' age and discussion with doctors about lung cancer screening: Diminished returns of Blacks. Issue 1 (20th February 2019) - Chalian, Hamid; Khoshpouri, Pegah; Assari, Shervin
Abstract: Objective: As age is one of the main risk factors for lung cancer, older adults are expected to receive more messages regarding lung cancer screening (LCS). It is, however, unclear whether age similarly increases patients' chance of discussing LCS across various racial groups. We aimed to determine racial differences in the effect of patients' age on patient‐physician discussion about LCS. Methods: This cross‐sectional study borrowed data from the Health Information National Trends Survey 5 (HINTS 2017), which included 2277 adults. Patients' demographic factors, socioeconomic characteristics, smoking status, possible LCS indication, and patient‐physician discussion about LCS were measured. We ran logistic regression models for data analysis. Results: Independent of possible LCS indication, older patients were more likely to have a patient‐physician discussion about LCS. However, there was a significant interaction between race and age, suggesting a larger effect of age on the likelihood of discussing LCS with doctors for Whites than Blacks. In race‐stratified models that controlled for possible LCS indication, higher age increased lung cancer discussion for Whites but not for Blacks. Conclusion: Whether age increases the chance of discussing LCS or not depends on the patient's race, with Blacks receiving fewer messages regarding LCS as a result of their aging.